Lean implementation frameworks: The challenges for SMEs - Almanei, Mohammed; Salonitis, Konstantinos; Xu, Yuchun (Elsevier, 2017)
Implementation of lean manufacturing in any type of organizations can bring many benefits, such as reducing waste and improving operating efficiency. However, lean implementation is not a straightforward process. Although a number of frameworks have been presented, still many companies find it difficult to implement lean. Furthermore, most of these roadmaps are for large manufacturing companies, and not for small and medium enterprises. Unfortunately, there is not a recipe that if used can guarantee a successful implementation. Furthermore, unsuccessful implementation can have a great impact on organization's resources, but even more importantly, affect employees and their confidence in lean philosophy. In the present paper, the most prominent lean implementation frameworks will be discussed, under the prism of the needs of SMEs. The challenges for the SMEs in their lean journey are discussed. Paper originally presented at Manufacturing Systems 4.0 – Proceedings of the 50th CIRP Conference on Manufacturing Systems, held 3 – 5 May, 2017, Taichung City, Taiwan.
Keywords: Lean management; Lean implementation; Framework